The Influence of Transformational Leadership, Work Motivation and Physical Work Environment on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Pelindo Regional 1 (Persero) Belawan Branch - Chairunnisa , Chairunnisa; Dalimunthe, Ritha F.; Absah, Yeni (International Journal of Business and Applied Economics, 2025)
Factors that significantly impact employee performance include transformational leadership, intrinsic drive at work, and the physical work environment. An employee's level of job happiness is directly correlated to the level of performance they deliver. Using job satisfaction as an intermediary variable, this study aims to examine the impact of transformational leadership, work motivation, and the physical work environment on employee performance at the Belawan Branch of PT. Pelindo Regional 1 (Persero). The 52 participants who made up the sample were all permanent workers of the Belawan Branch of PT. Pelindo Regional 1 (Persero). Descriptive statistics and path analysis were used to analyze the data. Employee performance is positively and significantly impacted by transformational leadership, work motivation, and the physical work environment, according to the research.